2020
DOI: 10.1016/j.flowmeasinst.2019.101679
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigation of the metering characteristic and pressure losses of the rotary tubular spool valve

Abstract: This paper presents the results of numerical and experimental performance evaluation of the rotary tubular spool valve. The aim of this work is to develop further the novel design of the tubular spool valve by confirming experimentally the validity of the simulation model and its results, thereby proving the valve's potential to represent a feasible and more efficient alternative to conventionally used translation spool valves avoiding the use of two stage valve configurations. In this research the valve perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Many studies have investigated the flow in hydraulic components such as elbows (Korkmaz et al 2021;Perumal and Ganesan 2016;Zahedi et al 2019), pipes (Düz 2019), bends (Reghunathan Valsala et al 2019Rinaldi et al 2019;Tarodiya et al 2020), Tjunctions Ŝtigler et al 2012) and valves (Okhotnikov et al 2020). Besides, studies on hydraulic filters have mainly examined the design (Momin et al 2017), optimization (Tekelioğlu et al 2020), clogging properties (Eker et al 2016), and strength (Momin et al 2017), in addition to fatigue (Park 2002), and contamination (Singh et al 2012;Zhang et al 2018).…”
Section: 𝛽 = 𝑁 𝑑 𝑈 𝑁 𝑑 𝐷mentioning
confidence: 99%
“…Many studies have investigated the flow in hydraulic components such as elbows (Korkmaz et al 2021;Perumal and Ganesan 2016;Zahedi et al 2019), pipes (Düz 2019), bends (Reghunathan Valsala et al 2019Rinaldi et al 2019;Tarodiya et al 2020), Tjunctions Ŝtigler et al 2012) and valves (Okhotnikov et al 2020). Besides, studies on hydraulic filters have mainly examined the design (Momin et al 2017), optimization (Tekelioğlu et al 2020), clogging properties (Eker et al 2016), and strength (Momin et al 2017), in addition to fatigue (Park 2002), and contamination (Singh et al 2012;Zhang et al 2018).…”
Section: 𝛽 = 𝑁 𝑑 𝑈 𝑁 𝑑 𝐷mentioning
confidence: 99%
“…On the other hand, multiway valves generally possess more intricate flow channel configurations than traditional valves. As the coolant flows through a multiway valve, the fluid frequently undergoes multiple changes in flow direction, which unavoidably leads to high local pressure loss [9]. Numerous studies have already demonstrated the significant impact of pressure drop and heat transfer loss caused by valves or pipelines on the performance of ITMSs for EVs [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Edvardsen et al [20] measured the pressure drop in the shut-in valve at 55 kPa. The pressure losses in rotary tubular spool valves [9], reversing valves [21], and Tesla valves [14] are proportional to the flow rate and viscosity of the fluid, and inversely proportional to the change in flow area [22]. Moreover, Liu et al [23] demonstrated that triangular rib tubes have lower pressure loss than square pipes.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the flow in pipeline systems. These works can be classified as straight pipe (Kitoh 1991), bends at different angles (Valsala et al 2019;Röhrig et al 2015;Liu et al 2019;Rinaldi et al 2019), elbow (Zahedi et al 2019), Tjunctions (Štigler et al 2012), manifold (Zardin et al 2017;Zhang et al 2019) valve (Okhotnikov et al 2020;Lisowski andRajda 2013) etc. Valsala et al 2019 studied the flow characteristics in a tube with a 90° bend, examining the effects of vane number and shape on pressure loss.…”
Section: Introductionmentioning
confidence: 99%
“…Murakami et al (1969) examined an experimental study about the flow in the commercial elbows, comparing the head loss and flow characteristics of a single elbow and two elbows. Okhotnikov et al (2020) performed an experimental and numerical study of a rotary tubular spool inside a valve. Flow and pressure losses in the valve, according to the angular positions of the spool, were investigated in their study.…”
Section: Introductionmentioning
confidence: 99%